SULAM UMPSA Fostering A Civic Minded Graduates - Hadijah, Ahmad (UMPSA, 2024)
Service learning is a well-known integrated approach to modern teaching and learning strategies. The history of service learning began with scholars like Ernest Boyer, who challenged American colleges to shift their focus beyond just preparing students for careers. In his view, education reform should be oriented towards producing citizens with a civic minded mentality who are capable of listening, caring, and contributing to the betterment of society.